PENGEMBANGAN MEDIA E-MAGAZINE PADA MATERI GETARAN, GELOMBANG DAN BUNYI DI KELAS VIII SMP - Rasidi Rasidi; Tomo Djudin; Syaiful B Arsyid (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThis study discusses the development of e-magazine learning media (ElectronicMagazine). E-Magazine is an electronic version of the magazine because it is based onelectricity. Electronic magazines no longer use raw materials in the form of paper butin the form of digital files. This study aims to develop an e-magazine on Vibration,Waves and Sound at SMP Negeri 8 Pontianak and to find out the responses and learningoutcomes of class VIII students to development that adapts the ADDIE framework ofthinking which consists of the stages of analysis, design, development, implementation,evaluation. The research instruments used were observation sheets, interviews andquestionnaires. The results showed that the evaluation of e-magazines according tomedia experts, material experts, and teacher assessments each obtained an averageanswer score of 4.1 (good); 4.3 (very good); 4.8 (very good) then the percentage ofstudent response scores obtained by 83.3% (very good) and the learning outcomes ofpre-test and post-test students respectively were 58.5 and 77.2 an increase in learningoutcomes. Based on the overall development process, it can be concluded that the e-magazine developed and based on the responses of class VIII students is very well usedas a learning resource.Keywords: Development, E-magazine, Vibration, Waves and Sound